Quantitative Methods for Recoverable Hydrocarbon Reserves Evaluation and Area Selection of Shale under In-situ Conversion Conditions - Lianhua Hou; Zhongying Zhao; Xia Luo; Jingkui Mi; Zhenglian Pang; Lijun Zhang; Senhu Lin (Scientific Research, New Technologies and Applications Vol. 9, 2024)
In the United States, the “shale revolution” made commercial development of shale oil and gas possible, and changed the world’s energy supply and geopolitical structure. Shale oil and gas has become a high-focus area of exploration and development, and an important means of increasing oil and gas reserves and production in the world. In terms of the extensively developed immature to low-moderate continental shale in China, the organic matter mainly exists in the solid state, and it is difficult for the existing horizontal well hydraulic fracturing technology to achieve large-scale cost-effective development. However, even though in-situ conversion technology is feasible, the methods and key parameters of the area selection and assessment of recoverable hydrocarbon reserves in immature to low-moderate maturity in-situ converted shales have not been determined. In this chapter, based on thermal simulation experiments of shale and crude oil under in situ conversion conditions, methods for assessing recoverable hydrocarbons and selecting favorable areas through the in situ conversion of immature to low–moderate-maturity shales were established. First, relationships between the in situ-converted total organic carbon (TOC) content and the vitrinite reflectance (Ro) of the shales and between the residual oil volume and the hydrocarbon yield were established. Second, the yields of residual oil and in situ-converted hydrocarbon were measured, revealing their sensitivity to fluid pressure and crude oil density. In addition, a model was proposed to estimate the amount of in situ-converted hydrocarbon based on TOC, hydrocarbon generation potential, Ro, residual oil volume, fluid pressure, and crude oil density. Finally, a method was established to determine key parameters of the final hydrocarbon yield from immature to low–moderate-maturity organic material during in situ conversion in shales. Following the procedure outlined in this paper, the estimated recoverable in situ-converted oil in the shales of the Nenjiang Formation in the Songliao Basin was estimated to be approximately 292 × 108 tons, along with 18.5 × 1012 cubic meters of natural gas, in an area of approximately 8 × 104 square kilometers. The results can provide a practical and theoretical basis for the implementation of in situ conversion operations in immature to low-maturity shale in the Nenjiang Formation and can serve as a guideline for the entire Songliao Basin, as well as universally around the globe on other shale formations where thermal simulation experiments have not been conducted.